Comparison of three maps at multiple resolutions: a case study of land change simulation in Cho Don District, Vietnam - Pontius, R.G. Jr; Peethambaram, S.; Castella, J.C. (Informa UK Limited, 2011)
Geographic modelers frequently compare maps of observed land transitions to maps of simulated land transitions to relate the patterns in reference maps to the output from a simulation model. Pixel-by-pixel analysis of raster maps at a single resolution is useful for this task at a single scale, but scientists often need to consider additional scales. This article presents methods to satisfy this need by proposing a multiple-resolution method to compare land categories in three maps: a reference map of time 1, a reference map of time 2, and a simulation map of time 2. The method generates a three-dimensional table that gives the percentage of the study area for each combination of categories at the maps' native resolution and at several nested sets of coarser squares. The method differentiates allocation disagreement within coarse squares, allocation disagreement among coarse squares, quantity disagreement, and agreement. We illustrate the method with output from a run of the SAMBA agent-based model from 1990 to 2001 using 32-m resolution pixels for Cho Don District, Vietnam. Results show that half of the overall disagreement is attributable to allocation disagreement within squares that are 506 m 506 m, which is about the average size of a village. Much of the remaining disagreement is misallocation of forest and shrub between the northern and southern parts of the district, which is caused by differences between the data and the simulation concerning transitions from the crop and shrub categories.